Sports and clean environment: Key drivers of health and longevity in the European Union - Alexandra Gabriela Milon; Cristian Mihai Dragoş; Vincenţiu Andrei Vereş; Leonina Baciu; Roxana Mare (Amfiteatru Economic, 2024)
This article highlights the effects of sports participation and environmental health on the lifespan and overall health of the population of the member states of the European Union. Utilizing data from 2010 to 2022, the study covers all EU countries, offering a comprehensive overview of the region's health dynamics. Through descriptive analyses of geographic distributions of indicators and panel data econometrics, clear continental disparities emerge, notably between the Northwest and Southeast regarding both the frequency of sports activity and environmental health conditions. To mitigate the potential confounding effects resulting from the strong correlations between the variables sports and environment variables and the gross domestic product per capita, the variables were standardised. This methodological consideration ensures a more accurate assessment of the direct impacts of sports participation and environmental health on lifespan and disability-adjusted life expectancy. The regression results reveal highly significant positive influences of population participation in sports and environmental health status on both lifespan and health quality, confirming the research hypotheses. Among control variables, the most statistically significant include health financing, the overall institution quality, sports funding, and lifestyle indicators.
Keywords: I15; Q56; Z20; 330; environmental quality; life expectancy; panel data; public health; sports